VARIATION OF RIAU MALAY LANGUAGE IN ROKAN HILIR REGENCY - Nurmayana . .; Amrin . Saragih; Sri Minda Murni (Universitas Negeri Medan, 2021)
ABSTRACTLanguage variation is the study of those features of language that differ systematically as compare different groups of speaker or the same speaker in different situation. As a multicultural country, Indonesia has so much variety of language. In addition to the official language, Indonesian people also have regional languages in each region. Rokan Hilir is one of them. Rokan Hilir, where the majority of the population is Malay, has a special regional language, namely the Malay language. This descriptive qualitative study identifies the variation of Riau Malay language in Rokan Hilir Regency review by analyze realizations of variation Riau Malay language in Rokan Hilir Regency. To understand the Realization of variation Riau Malay language in Rokan Hilir observation and interview were used in this study. The result indicates that realization of language variation were found there, phonology that is found as the most kinds of realization of language variation for about 21 times appearing or (53.8 %). Followed by Lexical 16 times or 41.1%, then grammar only found 2 times or 5.1% Keywords: Language Variation, Riau Malay Language, Rokan Hilir